2018
DOI: 10.1038/s41598-018-24342-x
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation reverses antibiotic and chemotherapy-induced gut dysbiosis in mice

Abstract: Fecal microbiota transplantation (FMT) is now widely used to treat recurrent Clostridium difficile infection, but has been less studied as a means to restore microbiome diversity and composition following antibiotic or chemotherapy treatments. The purpose of our study was to assess the efficacy of FMT to reverse antibiotic- and chemotherapy-induced gut dysbiosis in a mouse model. C57BL/6J mice were treated with ampicillin for 1 week and/or received a single intraperitoneal injection of 5-Fluorouracil. Fresh st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 66 publications
3
90
0
Order By: Relevance
“…When testing these three microbiota modulation strategies, different changes were observed in the bacterial metaproteome, demonstrating that every single change in the host environment can affect microbiota function. In addition to results observed over a short-term period of time [16,18], these findings show that a HFD has a major impact on the mouse cecal microbiota that extends beyond compositional changes to major alterations in bacterial physiology, and FMT can be considered a new strategy to treat obesity.…”
Section: Resultssupporting
confidence: 56%
“…When testing these three microbiota modulation strategies, different changes were observed in the bacterial metaproteome, demonstrating that every single change in the host environment can affect microbiota function. In addition to results observed over a short-term period of time [16,18], these findings show that a HFD has a major impact on the mouse cecal microbiota that extends beyond compositional changes to major alterations in bacterial physiology, and FMT can be considered a new strategy to treat obesity.…”
Section: Resultssupporting
confidence: 56%
“…How to cope with opportunistic infection from the gut commensal bacteria remains unsolved in the elderly. In general, it would be realized by fecal microbiota transplantation [42], but more practical by probiotic supplementation [43] and dietary fiber consumption [44]. This study, showing a promise outcome of the natural and clean MW for the better control of gut bacteria, provides a convenient and safe choice to prevent the early onset of breast cancer by curating a high-fat diet-and red meat-induced gut dysbiosis [45,46].…”
Section: Resultsmentioning
confidence: 91%
“…Another side‐effect of antibacterial agents is that they unbalance the gut microbiota (Jernberg, et al , ; Macfarlane, ). For instance, ampicillin and gentamicin cause a significant and immediate decrease in bacterial species richness and diversity (Johnson, et al , ; Le Bastard, et al , ). It has been shown that even short‐term antibiotic administration has long‐term impacts on the gut microbiome (Jakobsson, et al , ).…”
Section: Discussionmentioning
confidence: 99%